Situation Report: Czechoslovakia, 12 May 1960 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Rude Pravo Criticism of Agitprop 15th Anniversary of CS Liberation Celebrated in Congo Soured by a Critical Speech of a Congolese Politician Strougal, the CS Minister of Agriculture in Sofia CS Standard of Living Thieves Sentenced